MORPHOLOGICAL CHANGES OF THE RETINA IN TOXIC HEPATITIS (American Journal of Pedagogical and Educational Research, 2025)
Toxic hepatitis is accompanied not only by liver damage but also by systemic disorders, including alterations in the visual system. In recent years, special attention has been paid to the morphological changes in the retina, as it is a highly sensitive structure reflecting the general condition of the organism. In toxic liver injury, degenerative processes, photoreceptor dystrophy, disturbances of the retinal pigment epithelium, microcirculatory disorders, and enhanced apoptosis of nerve cells are observed. Histological and histochemical studies reveal imbalances in protein, lipid, and carbohydrate metabolism, leading to structural and functional insufficiency of the retina.